Human Factors Related to Cybersickness Tolerance in Virtual Environment - Ng, Adrian K. T.; Leung, Cheryl H. Y.; Chan, Leith K. Y.; Lau, Henry Y. K. (2022 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2022)
Sleep quality, spatial ability, and pain sensitivity had been suggested to affect cybersickness discomfort. This study evaluated various human factors on the cybersickness symptoms and tolerance duration in a nausegenic virtual environment. Results showed that participants with better sleep quality had better cybersickness tolerance. Further, participants with lower pain threshold had slightly lower cybersickness tolerance and reported more cybersickness symptoms.